ANALISIS PENGARUH PEMBERIAN INSENTIF DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN (Studi pada PT. PLN (Persero) Distribusi Jateng & DIY) - Ermawaty, Dinny Ardian; Nugraheni, Rini (Diponegoro Journal of Management, 2015)
This study aimed to analyze the effect of incentives and non-physical work environment on job satisfaction and employee performance in PT. PLN (Persero) Distribution Central Java and Yogyakarta. Hypothesis testing is done by distributing questionnaires as much as 100. The analysis used is the result of validity test, reliability test, the hypothesis test with the aid of SPSS version 20 computer using multiple linear regression analysis.Based on calculation of data and analysis used, the regression equation is:Y = 0.474 X1 + 0.399 X2 (the regression I)Y = 0.220 + 0.335 X1 + 0.412 X2 Y1 (regression II)By using multiple regression analysis, it can be concluded that the variable incentive positive effect on job satisfaction with 5,873 tvalue greater than 1,661 ttable with figures of significance 0,000 < 0,05. Variable non-physical work environment positive effect on job satisfaction 4,943 tvalue greater than ttable. Variable incentive positive effect on employee performance with tvalue 2,854 greater than ttable. Variable non-physical work environment positive effect on employee performance with tvalue 4,510 greater than ttable. And variable job satisfaction has positive influence on employee performance with tvalue 4,510 greater than ttable.It can be concluded that the variable incentives, non-physical work environment and job satisfaction have a significant influence on the performance of employees at PT. PLN (Persero) Distribution Central Java and Yogyakarta.